2022
DOI: 10.1103/physrevb.106.064403
|View full text |Cite|
|
Sign up to set email alerts
|

Neutron diffraction in MnSb2O6 : Magnetic and structural domains in a helicoidal polar magnet with coupled chiralities

Abstract: MnSb 2 O 6 is based on the structural chiral P321 space group No. 150 where the magnetic Mn 2+ moments (S = 5/2, L ≈ 0) order antiferromagnetically at T N = 12 K. Unlike the related iron based langasite (Ba 3 NbFe 3 Si 2 O 14 ) where the low-temperature magnetism is based on a proper helix characterized by a time-even pseudoscalar "magnetic" chirality, the Mn 2+ ions in MnSb 2 O 6 order with a cycloidal structure at low temperatures, described instead by a time-even vector "magnetic" polarity. A tilted cycloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The precursor MnSb 2 O 6 film is composed of Sb metal and Mn­(OH) 2 with a 1:2 molar ratio, which react to form crystalline MnSb 2 O 6 during annealing in air at 700 °C . All the Mn sites in the MnSb 2 O 6 crystal structure are isolated from other Mn sites with a nearest Mn–Mn distance of ∼4.7 Å. , The scanning electron microscopy (SEM) images of the MnO 2 and MnSb 2 O 6 films used in this study are shown in Figures S1–S2. Other characterization results for MnO 2 and MnSb 2 O 6 are available elsewhere. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The precursor MnSb 2 O 6 film is composed of Sb metal and Mn­(OH) 2 with a 1:2 molar ratio, which react to form crystalline MnSb 2 O 6 during annealing in air at 700 °C . All the Mn sites in the MnSb 2 O 6 crystal structure are isolated from other Mn sites with a nearest Mn–Mn distance of ∼4.7 Å. , The scanning electron microscopy (SEM) images of the MnO 2 and MnSb 2 O 6 films used in this study are shown in Figures S1–S2. Other characterization results for MnO 2 and MnSb 2 O 6 are available elsewhere. , …”
Section: Resultsmentioning
confidence: 99%
“…33 All the Mn sites in the MnSb 2 O 6 crystal structure are isolated from other Mn sites with a nearest Mn−Mn distance of ∼4.7 Å. 36,37 To initially assess the activity of these films for water and glycerol oxidation at various pH conditions and determine which potentials should be used for constant potential glycerol oxidation, linear sweep voltammetry (LSV) was carried out at pH 1, 4, 7, 10, 13, and 14 (Figure 1). The intermediate pH conditions (4, 7, and 10) were buffered to maintain the pH throughout the experiments (see the Experimental Section for electrolyte preparation details).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To unambiguously relate the magnetic chirality to the structural chirality, the latter needs to be determined by analyzing the Schwinger scattering of adequate reflections (see, e.g., Refs. [31,32]). We have identified several reasonably strong (hkl) reflections revealing a flipping ratio asymmetry of |R − 1| > 0.04 which would be experimentally feasible.…”
Section: Discussionmentioning
confidence: 99%